Early Intervention by Counsel: A Multi-Site Evaluation of the Presence of Counsel at Defendants' First Appearance (CAFA) in Court, 6 New York State counties, 2012-2016 - Worden, Alissa Pollitz ([Verlag nicht ermittelbar], 2020)
This study sought to assess the impact of local programs that ensure that legal counsel is provided at first appearance (usually arraignment) in court on court decisions (such as bail or pretrial release, and consequences such as pretrial detention and booking at a local detention facility), as well as on subsequent consequences for charge reduction, disposition, and sentencing. The project collected original data from six upstate New York counties (under pseudonyms). The data were collected from indigent defense programs' case files, supplemented by data from county detention facilities on booking and release. Demographic variables in this collection include defendant age, race, gender, and residency.